Seven wonders of Ulug-Khem - Saryglar, Sh.; Ivanova, M.; Maadyr, Sh.; Tulush, S.-B. (The New Research of Tuva, 2013)
Article by the students of Shagonar secondary school #1 presents the project they initialized at the "My Earth”forum (campaign "Cher” – "The Earth”). They made a selection of seven natural and cultural objects of Ulug-Khem district and gathered information about them.